Views on BIM, procurement and contract management - Olatunji, Oluwole (Thomas Telford, UK, 2014)
Building information modelling (BIM) offers a pathway to change in extant technical operations (and business practices) in the architectural, engineering, construction and facilities operations disciplines. Published evidence markedly suggests BIM enhances project outcomes and contract relationships, as though this is a considerable departure from conventional challenges. The overarching question explored in this research – what is this change really about and who does it affect? – is aimed at expounding the relationship between BIM-triggered change and existing change management theories. Although construction disciplines react to change differently, and so are different business structures, the context of change facilitated by BIM is identifiable. It includes behavioural change, process change and role change. Others include skill change, tool change and product change. Furthermore, there are project change scenarios, BIM-triggered change to business models and philosophies and change to legal frameworks. These variables and their descriptors are both interactive and ontologically stratified. Thus, more contemporary studies should reflect the characterisations in these changes. In the end, conclusions are drawn on the legal implications of the different scenarios of BIM changes and potential areas for further research.